Active site engineering and theoretical aspects of ``Superhydrophilic'' nanostructure array enabling efficient overall water electrolysis - Barik, Sidharth; Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Singh, Chandrodai Pratap; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2023)
The rational design of noble metal-free electrocatalysts holds great promise for cost-effective green hydrogen generation through water electrolysis. In this context, here, the development of a superhydrophilic bifunctional electrocatalyst that facilitates both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline conditions is demonstrated. This is achieved through the in situ growth of hierarchical NiMoO4@CoMoO4 center dot xH(2)O nanostructure on nickel foam (NF) via a two-step hydrothermal synthesis method. NiMoO4@CoMoO4 center dot xH(2)O/NF facilitates OER and HER at the overpotentials of 180 and 220 mV, respectively, at the current density of 10 mA cm(-2). The NiMoO4@CoMoO4 center dot xH(2)O/NF parallel to NiMoO4@CoMoO4 center dot xH(2)O/NF cell can be operated at a potential of 1.60 V compared to 1.63 V displayed by the system based on the Pt/C@NF parallel to RuO2@NF standard electrode pair configuration at 10 mA cm(-2) for overall water splitting. The density functional theory calculations for the OER process elucidate that the lowest Delta G of NiMoO4@CoMoO4 compared to both Ni and NiMoO4 is due to the presence of Co in the OER catalytic site and its synergistic interaction with NiMoO4. The preparative strategy and mechanistic understanding make the windows open for the large-scale production of the robust and less expensive electrode material for the overall water electrolysis.
Keywords: density functional theory (DFT) study; hydrogen evolution reaction (HER); Hydrothermal synthesis; oxygen evolution reaction (OER); superhydrophilic nanostructures; synergistic interaction; water electrolysis

Breaking the Pt electron symmetry and OH spillover towards ptir active center for performance modulation in direct ammonia fuel cell - Barik, Sidharth; Kharabe, Geeta Pandurang; Samal, Pragnya Paramita; Urkude, Rajashri R.; Kumar, Sachin; Yoyakki, Athira; Vinod, C. P.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Small, 2024)
The growing interest in low-temperature direct ammonia fuel cells (DAFCs) arises from the utilization of a carbon-neutral ammonia source; however, DAFCs encounter significant electrode overpotentials due to the substantial energy barrier of the *NH2 to *NH dehydrogenation, compounded by the facile deactivation by *N on the Pt surface. In this work, a unique catalyst, Pt4Ir@AlOOH/NGr i.e., Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles controllably decorated on the pseudo-boehmite phase of AlOOH-supported nitrogen-doped reduced graphene (AlOOH/NGr) composite, synthesized via the polyol reduction method. The detailed studies on the structural and electronic properties of the catalyst by XAS and VB-XPS reveal the possible electronic modulations. The optimized Pt4Ir/ANGr composition exhibits a significantly improved onset potential and mass activity for AOR. The DFT study confirms the OHad species spillover by AlOOH and Pt4Ir (100) facilitates the conversion of the *NH2 to *NH with minimal energy barriers. Finally, testing of DAFC at the system level using a membrane electrode assembly (MEA) with Pt4Ir/ANGr as the anode catalyst, demonstrating the suitability of the catalyst for its practical applications. This study thus uncovers the potential of the Pt4Ir catalyst in synergy with ANGr, largely addressing the challenges in hydrogen transportation, storage, and safety within DAFCs. In this article, a versatile catalyst, Pt4Ir/ANGr, is introduced composed of PtIr alloy nanoparticles decorated on AlOOH/NGr composite. The AlOOH provides an -OH-rich surface conducive to the facile adsorption and decoration of the PtIr alloy nanoparticles and OHad species spillover from AlOOH to the Pt4Ir active center during AOR, further validating the higher experimental activity obtained in Pt4Ir/ANGr. image
Keywords: ammonia oxidation reaction (AOR); d-band center; density functional theory (DFT) study; direct ammonia fuel cells; hydroxyl spillover effect; XAS analysis